1995
DOI: 10.3109/00207459508986335
|View full text |Cite
|
Sign up to set email alerts
|

The Pineal Gland, Cataplexy, and Multiple Sclerosis

Abstract: Since the discovery of melatonin as the principal hormone of the pineal gland in 1963, scientists have come to recognize that melatonin is a "master hormone" involved in the control of circadian rhythms and other biological functions. Although little is known about the influence of the pineal gland on motor control, important clues may be obtained by considering the pattern of melatonin secretion during the sleep cycles and particularly during rapid eye movement (REM) sleep when melatonin plasma levels are at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 96 publications
1
5
0
1
Order By: Relevance
“…Patients with RLS may respond to low doses of dopaminergic agonists. In a recent unpublished study, a central hypersomnia associated with sleepiness was found in some patients [Stankoff et al unpublished data] corroborating previous description of patients with MS and narcolepsy/cataplexy [Sandyk, 1995]. Such patients, who remain to be described more precisely, should respond better to molecules that promote wakefulness, such as modafinil.…”
Section: Pharmacological Treatmentsupporting
confidence: 64%
“…Patients with RLS may respond to low doses of dopaminergic agonists. In a recent unpublished study, a central hypersomnia associated with sleepiness was found in some patients [Stankoff et al unpublished data] corroborating previous description of patients with MS and narcolepsy/cataplexy [Sandyk, 1995]. Such patients, who remain to be described more precisely, should respond better to molecules that promote wakefulness, such as modafinil.…”
Section: Pharmacological Treatmentsupporting
confidence: 64%
“…Cataplexy-like episodes may be described by patients with MS, such as weakness in the legs and neck, feeling of collapsing knees, paroxysmal sudden falling, extreme fatigue, intermittent paresthesias, slurring of speech, and intermittent blurring of vision. Both may be exacerbated by sudden emotions [13]. Further research and clinical studies are needed to clearly understand the nature of sleep disturbances and excessive sleepiness in MS.…”
Section: Sleep Disorders In Multiple Sclerosismentioning
confidence: 97%
“…A rare form of generalized PW is cataplexy. In addition to be a symptom of narcolepsy, a comorbid condition with MS, cataplexy has been described as a paroxysmal symptom in MS patients with lesions affecting the hypothalamus or reticular activating system (i.e., within the pons and midbrain) [ 51 ]. Treatment with clomipramine was used to control cataplectic attacks in one patient [ 51 ].…”
Section: Paroxysmal Symptoms Categoriesmentioning
confidence: 99%